Error Analysis of Radar Coincidence Imaging in the Presence of Noise - Dai Qiang; Cheng Yong-qiang; Qin Yu-liang; Wang Hong-qiang; Li Xiang (Leida xuebao, 2014)
Radar coincidence imaging is a new method for high-resolution staring imaging. First, the mathematical model is constructed. Second, the theoretical error for radar coincidence imaging in the presence of noise is derived using the parametric imaging method. Third, the factors that affect the error are analyzed. Fourth, the sparse reconstruction algorithm is used to perform numerical simulations of radar coincidence imaging with different parameters. Finally, the effects of signal bandwidth, array configuration, size of the imaging unit, and target complexity on image error in the presence of noise are discussed. This study provides the theoretical framework for parameters selection and SNR requirements for radar coincidence imaging systems.